The Use of the North Sumatra E-Museum on Resource Reading Skills in Anthropology - Maswita Maswita; Hasrita Lubis (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this research is to prove the improvement of reading skills of Al-Azhar University law students through the e-Museum. A post-test research design with only a control design is the quantitative experimental approach used in this method. Primary school students in the second grade served as the study population; they were split evenly into two groups (20 in the experimental group and 18 in the control group). The normality test, homogeneity test, and paired sample t-test are the data analysis methods used to determine the value of Sig. (2-tailed), where a value of 0.000 0.05 indicates that Ha is accepted and Ho is rejected. There were also notable differences between the control and experimental groups. It concluded that the e-Museum could help law students in their anthropological classes become better readers. This means that everyone accessing the E-museum needs to pay close attention to its digitally recorded and easily accessible archive of historically significant, scientifically significant, and culturally significant visual and aural materials.